Perancangan Sistem Informasi Wisata Kuliner Berbasis Website di Kota Makassar Sebagai Media Promosi dan Informasi - Muhammad Reza Zadillah Putra; Valentino Aris; Muhammad Jamil (Journal of Innovative and Creativity, 2026)
The problem addressed in this study is the lack of comprehensive and clear culinary tourism information media in Makassar City. This study aims to design a website as an information medium for tourists and as a promotional medium for culinary businesses. Using the Research and Development (R&D) method with the ADDIE model. Validation results by three validators showed that all tested features functioned properly. Evaluation using the System Usability Scale (SUS) yielded a score of 81.41, indicating a good level of usability.